Effects of Cotton Growth Regulator on Jassid Infestation and Injury - Eittipibool, Weerawan; Renou, Alain; Chongrattanameteekul, Wiboon; Hormchan, Praparat (Agriculture and Natural Resources, 2001)
Six upland cotton cultivars with different morphological characters were tested during the cotton growing season of 1998 to determine the changes in leaf characters due to plant growth regulator. Mepiquat chloride (cotton growth regulator) sprayed at first flowering stage reduced mid vein and hair lengths on lamina as well as on mid vein but increased lamina thickness and hair density on mid vein. Cotton growth regulator did not show significant effect on jassid infestation. Jassid injuries were higher in treated plots but the results were not significant. No interaction between cultivar and growth regulator spray was observed. Cultivar differences on jassid infestation and injury were highly significant. The cotton growth regulator mainly reduced the number of jassid eggs laid per leaf. However, mid vein shortening seemed to be more responsible for lowering egg deposition than changes in leaf hairiness.